Can the Tripartite Free Trade Area (TFTA) Agreement Become a Breakthrough Arrangement in Regional Integration on the African Continent? - Folfas, Paweł Jan; Garlińska-Bielawska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Concluded in 2015, the Tripartite Free Trade Area (TFTA) agreement between three regional trade arrangements in Africa (COMESA, SADC, EAC) is the first step towards creating the Continental Free Trade Area (CAFTA), planned for 2017. This article attempts to assess the importance of the TFTA agreement for the process of regional integration in Africa. The article uses an analytical and descriptive method on the basis of domestic and foreign literature sources and statistics of the United Nations Conference on Trade and Development (UNCTAD). Empirical studies were also conducted with the use of the Regional Trade Introversion Index (RTII). The analysis performed leads to the conclusion that the broad scope of both subjects and countries covered by the Tripartite agreement indicates that it may be a step towards a new development strategy for regional integration in Africa. However, the authors’ own study results suggest that the position of the agreement in world trade will remain unchanged.